2007
DOI: 10.1016/j.atherosclerosis.2006.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery plaque thickness is associated with increased serum calcium levels: The Northern Manhattan study

Abstract: Serum calcium levels in a multi-ethnic population of older men and women were positively associated with carotid plaque thickness, a powerful early predictor of clinical coronary and cerebrovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 40 publications
6
62
0
2
Order By: Relevance
“…(40) However, serum calcium and/or phosphate concentrations have been associated with increased carotid artery plaque thickness (1) and increased incidence of cardiovascular events and death in large retrospective (3,4) and prospective cohorts (2,41) in the general population. Primary hyperparathyroidism is another condition with increased serum calcium concentrations and has been associated with increased risk of cardiovascular events and death, (5,6) although evidence for increased vascular calcification is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(40) However, serum calcium and/or phosphate concentrations have been associated with increased carotid artery plaque thickness (1) and increased incidence of cardiovascular events and death in large retrospective (3,4) and prospective cohorts (2,41) in the general population. Primary hyperparathyroidism is another condition with increased serum calcium concentrations and has been associated with increased risk of cardiovascular events and death, (5,6) although evidence for increased vascular calcification is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Serum calcium concentrations are positively associated with increased carotid artery plaque thickness (1) and with increased incidence of myocardial infarction (MI) and death. (2)(3)(4) An increased risk of cardiovascular events and death also has been reported in primary hyperparathyroidism, a condition in which serum calcium is elevated.…”
Section: Introductionmentioning
confidence: 99%
“…A high calcium diet has been shown to increase serum calcium concentrations [46]. Calcium concentrations, in turn, have been positively associated with mineralization of vascular smooth muscle [48], carotid artery plaque thickness [49], and coronary artery disease burden [50].…”
Section: Discussionmentioning
confidence: 99%
“…[17] Recently, the clinical implications of increased calcium levels in CVD have extended into the normal ranges after findings of functional and structural changes in the vasculature. [11] Previous studies reported that high normal calcium levels are associated with greater pulse wave velocity in 9165 Chinese subjects, [18] carotid plaque thickness in 1194 multiethnic subjects, [19] and increased risk of left ventricular hypertrophy in 833 Chinese diabetic subjects. [20] Recent data from a longitudinal study of 1507 middle-aged Japanese men, which found changes in brachialankle pulse wave velocity during a 3-year follow-up period, further highlight the possibility that increased serum calcium may be involved in the pathogenesis of atherothrombosis.…”
Section: Discussionmentioning
confidence: 99%